Intraocular pressure, eye pain and hemodialysis - E. V. Kozina; P. M. Balashova; S. V. Ivliev (Российский офтальмологический журнал, 2022)
The review presents data on the effect of program hemodialysis on the state of intraocular pressure in patients with terminal chronic renal failure. Treatment with hemodialysis is accompanied by various effects: from intraocular pressure drop to the development of ophthalmic hypertension with pain syndrome. The state of the iris-corneal angle, neovascularization of the structures of the eye drainage system and the presence of glaucoma are significant, but not indisputable, risk factors for pain-related dialysis ophthalmic hypertension. Their combination with the effect on the osmolar balance of dialysis therapy increases the possibility of the formation of ocular hypertension syndrome formation. The need to eliminate dialysis eye pains and the chance of glaucoma progression due to dialysis-affected fluctuations of intraocular pressure remains relevant.